Methane production and energy balance in crossbred male calves fed on rations containing different ratios of green sorghum and wheat straw - HAQUE, N; SARASWAT, M L; SAHOO, A (The Indian Journal of Animal Sciences, 2014)
Growing crossbred (Holstein FriesianxHariana) male calves (8) weighing 225kg were divided into 2 groups of 4 each to study the methane production and energy bal;mce in crossbred calves fed on diets having 2 different ratios of wheat straw and sorghum. Green sorghum and wheat straw were in the ratio of 90: 10 in group 1 and 60:40 in group 2. Both the rations were supplemented with wheat bran. The dry matter intake was 93.9Â±4.49 and 95.5Â±8.33 g/kg W0.75/d in groups 1 and 2 respectively. The digestibility of DM, OM, CP and NFE were significantly (P